Anti‐SARS‐CoV‐2 Inhibitory Profile of New Quinoline Compounds in Cell Culture‐Based Infection Models. Issue 4 (29th December 2021) - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana B.
Abstract: The presently ongoing pandemic of human SARS‐CoV‐2 infections (COVID‐19) presents an enormous challenge in surveillance, vaccine and antiviral drug development. Here we report the synthesis of new bioactive quinoline‐morpholine hybrid compounds and their virological evaluation, which proves pronounced cell culture‐based inhibitory profile against SARS‐CoV‐2. Thus, selected quinoline compounds may suggest specific hit‐to‐lead development. Abstract : New quinoline‐based compounds were synthesized via conventional synthetic methods, including copper‐catalyzed azide‐alkyne cycloaddition reactions (CuAAC) and were studied for their activity against SARS‐CoV‐2. These quinoline derivatives showed pronounced cell culture‐based inhibitory profiles against the virus (EC50 down to 1.5±1.0 μM), thus presenting a very promising developmental basis compared to reference drugs chloroquine (EC50 =3.1±2.7 μM).